Defining the risk of SARS-CoV-2 variants on immune protection - Ghedin, Elodie; Krammer, Florian; Grifoni, Alba; Alter, Galit; Baric, Ralph S.; Barouch, Dan H.; Bloyet, Louis-Marie; Bonenfant, Gaston; Boon, Adrianus C. M.; Boritz, Eli A.; Bratt, Debbie L.; Bricker, Traci L.; et al. (Nature (London), 2022)
The global emergence of many severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants jeopardizes the protective antiviral immunity induced after infection or vaccination. To address the public health threat caused by the increasing SARS-CoV-2 genomic diversity, the National Institute of Allergy and Infectious Diseases within the National Institutes of Health established the SARS-CoV-2 Assessment of Viral Evolution (SAVE) programme. This effort was designed to provide a real-time risk assessment of SARS-CoV-2 variants that could potentially affect the transmission, virulence, and resistance to infection- and vaccine-induced immunity. The SAVE programme is a critical data-generating component of the US Government SARS-CoV-2 Interagency Group to assess implications of SARS-CoV-2 variants on diagnostics, vaccines and therapeutics, and for communicating public health risk. Here we describe the coordinated approach used to identify and curate data about emerging variants, their impact on immunity and effects on vaccine protection using animal models. We report the development of reagents, methodologies, models and notable findings facilitated by this collaborative approach and identify future challenges. This programme is a template for the response to rapidly evolving pathogens with pandemic potential by monitoring viral evolution in the human population to identify variants that could reduce the effectiveness of countermeasures. The SARS-CoV-2 Assessment of Viral Evolution (SAVE) programme provides a real-time risk assessment of SARS-CoV-2 variants with the potential to affect transmission, virulence and resistance to infection- and vaccine-induced immunity.